A Theory of Optimum Currency Areas : Revisited - Flood, Robert (IMF Working Papers; Working Paper, 1992)
Starting with Friedman and Mundell the academic literature has conducted a high level debate concerning the design of cross-country monetary arrangements. That debate has become very complex and the data requirements necessary for appropriate application of the principles developed are far beyond the means of the very nations for which the principles might be valuable. In this paper we return to the simplicity of the early arguments and formalize them in a way that may be helpful for currency area decisions where little is known about economic structure.